2012
DOI: 10.1123/jpah.9.s1.s56
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Errors in Physical Activity Recall Data

Abstract: Modeling measurement error in recall data can be used to provide more accurate estimates of long-term activity behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 22 publications
1
90
3
Order By: Relevance
“…An attractive option is to correct for self-report bias in a calibration procedure and use the corrected exposure values for further analyses. Calibration, or exposure modeling, is an established method for correcting self-reported information in the field of nutritional and body composition (41,42) and in occupational hygiene (43)(44)(45), and it is becoming increasingly popular in the field of physical activity (46)(47)(48)(49), even in an occupational context (50)(51)(52). The present study contributes to the development of effective models for estimating "true" sedentary time and time in MVPA by identifying a number of factors that may, in addition to the self-reported exposure in its own right, influence the extent of self-report bias, and that may, therefore, be candidates for inclusion in calibration models.…”
Section: Gupta Et Almentioning
confidence: 99%
“…An attractive option is to correct for self-report bias in a calibration procedure and use the corrected exposure values for further analyses. Calibration, or exposure modeling, is an established method for correcting self-reported information in the field of nutritional and body composition (41,42) and in occupational hygiene (43)(44)(45), and it is becoming increasingly popular in the field of physical activity (46)(47)(48)(49), even in an occupational context (50)(51)(52). The present study contributes to the development of effective models for estimating "true" sedentary time and time in MVPA by identifying a number of factors that may, in addition to the self-reported exposure in its own right, influence the extent of self-report bias, and that may, therefore, be candidates for inclusion in calibration models.…”
Section: Gupta Et Almentioning
confidence: 99%
“…This is likely too optimistic an assumption and was used in our simulations to focus, specifically, on random measurement error. Other studies have shown evidence of systematic biases in self-reports of physical activity outcomes (Ferrari et al 2007;Nusser et al 2012;Tooze et al 2013), although they focused on data analyzed from convenience samples that are not representative of all adult Americans. To better understand measurement error properties of self-reported physical activity data in national surveys, multiple measurements from different points in time should be considered for at least a subsample of survey participants in order to distinguish measurement error and other forms of intra-individual variation in the data from actual variability in physical activity across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the terminology used in self-report questionnaires may be confusing or unclear, which can result in misreporting (Sallis and Saelens 2000). Self-reporting errors like these often result in much larger estimates of physical activity than those taken from more objective instruments like accelerometers or other monitoring devices and can fundamentally bias estimates of physical activity in adult populations (Ferrari et al 2007;Nusser et al 2012;Tooze et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 While there are limitations to measurement error models, they are becoming more established and can be used to correct for measurement error associated with parenting measures. 33,37,41 Structural equation modeling can provide an alternative approach to account for measurement error. For example, this is achieved by treating all survey items measuring parenting as a latent construct, meaning that the items are aggregated as one factor.…”
Section: Correcting For Social Desirability and Measurement Errorsmentioning
confidence: 99%